Limited Introgression between Rock-Wallabies with Extensive Chromosomal Rearrangements. (3rd December 2021) - Potter, Sally; Bragg, Jason G; Turakulov, Rustamzhon; Eldridge, Mark D B; Deakin, Janine; Kirkpatrick, Mark; Edwards, Richard J; Moritz, Craig
Abstract: Chromosome rearrangements can result in the rapid evolution of hybrid incompatibilities. Robertsonian fusions, particularly those with monobrachial homology, can drive reproductive isolation amongst recently diverged taxa. The recent radiation of rock-wallabies (genus Petrogale ) is an important model to explore the role of Robertsonian fusions in speciation. Here, we pursue that goal using an extensive sampling of populations and genomes of Petrogale from north-eastern Australia. In contrast to previous assessments using mitochondrial DNA or nuclear microsatellite loci, genomic data are able to separate the most closely related species and to resolve their divergence histories. Both phylogenetic and population genetic analyses indicate introgression between two species that differ by a single Robertsonian fusion. Based on the available data, there is also evidence for introgression between two species which share complex chromosomal rearrangements. However, the remaining results show no consistent signature of introgression amongst species pairs and where evident, indicate generally low introgression overall. X-linked loci have elevated divergence compared with autosomal loci indicating a potential role for genic evolution to produce reproductive isolation in concert with chromosome change. Our results highlight the value of genome scale data in evaluating the role of Robertsonian fusions and structural variation in divergence, speciation, and patterns of molecular evolution.